Common carp - Horvath, Laszlo (Food and Agriculture Organization of the United Nations, 1985)
This is the first part of an illustrated manual on the large-scale propagation of cyprinus carpio, the common carp. It particularly provides details about the advanced technology which has recently been developed in Hungary for the mass production of carp eggs and early fry through artificial reproduction in a modern hatchery.